2015
DOI: 10.1177/0363546515608476
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Shoulder Capsules Are Thicker and Stiffer in the Throwing Shoulders of Healthy College Baseball Players

Abstract: The posterior and posteroinferior capsules were stiffer as well as thicker in the throwing shoulder of college baseball players compared with the nonthrowing shoulder. Posterior capsule elasticity appeared to have a greater effect on GIRD than did posterior capsule thickness. This technology could be used as a noninvasive screening method for throwing athletes to identify players at potential risk of shoulder injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 30 publications
4
73
1
Order By: Relevance
“…These results are similar to previous studies. Conversely, Takenaga et al investigated the stiffness of the posterior and posteroinferior capsules in throwing shoulders of healthy college baseball players using SWE and reported that each capsule on the throwing side became stiffer than that on the nonthrowing side. In this study, we performed measurements using their methods.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to previous studies. Conversely, Takenaga et al investigated the stiffness of the posterior and posteroinferior capsules in throwing shoulders of healthy college baseball players using SWE and reported that each capsule on the throwing side became stiffer than that on the nonthrowing side. In this study, we performed measurements using their methods.…”
Section: Discussionmentioning
confidence: 99%
“…The hamstring muscles have a direct relationship with knee stability by working in synergy with the ACL in limiting anterior tibial translation [71]. Studies have shown the existence of a ligament muscle arc reflex between the ACL and the hamstrings, revealing the importance of this muscle group during ACL loading [72,73]. Moreover, recent guidelines for defining a successful outcome after ACL injury or reconstruction clearly show hamstring strength as an important target one and two years after ACL injury and reconstruction [74].…”
Section: Future Directions Andmentioning
confidence: 99%
“…ABER has also been shown to confer greater sensitivity and specificity for detection of partial-thickness rotator cuff tears (119,120) alternative to CT (125). Researchrelated applications have also been reported, such as shear-wave sonoelastography; Takenaga et al not surprisingly found that the posterior/posteroinferior capsules of throwing shoulders in collegiate baseball players were thicker and stiffer than those of the nonthrowing shoulders and that stiffness was more closely correlated to GIRD than thickness (126).…”
Section: Us and Ctmentioning
confidence: 99%